They are needed the nation resources allocated for compliance with the general participation system drinking water and basic saneamento (2015)
This document is based on the author's interest about the issue on the use of resources drawn from the General Revenue Sharing System for Drinking Water and Basic Sanitation (-APSB SGP), on the other hand an analysis is made of the resources that the Central Government transferred to the territorial, regional and municipal entities, based on the destination of the resources of the General System of Units for Potable Water and Sanitation (GSP APSB) administered by local authorities of the country where the term 2014.